Proposed Marketing Strategy for Calamus Factory Outlet in Order to Deal with Factory Outlet Business Competition in Bandung - Manan, Yudie Mohamad; Larso, Dwi (The Indonesian Journal of Business Administration, 2013)
Factory outlet industry in Bandung is growing rapidly year by year and had made a lot of new entrepreneurs running in the fashion industry, such as Calamus FO, Glow, Sahara, etc. Calamus FO is located Bandung, West Java. The rapid growth of the factoty outlet industry in Bandung makes the competition between them also increasingly tight. It can be seen from Calamus FO’s revenue for the last 2 years that has not reached the desired target of the shareholders. Therefore, the author will analyze the existing problems to find the root of the problem before finding the right marketing strategy. To analyze the issues, the author sees the factory outlet market conditions from a variety of sources. After seeing the condition of the existing factory outlet market, the author uses 5C analysis method (Company, Competitors, Customer, Collaborators, and Climate). From the analysis, it was founded that there are five roots of the problem which are: the product less following the trends, limited human resources, goods delivery that oftenly late, the location that far from the crowds of shopping center, and less comfortable conditions.Based on the root of the problem, the author proposed two marketing strategies that are interrelated. First, the author uses Porter's Generic Competitive Strategies as a reference to make the Calamus FO as a cost leadership among its competitors. Porter's Generic Competitive Strategies is useful for fashion entrepreneurs, which they could see their strengths to compete in the competitive fashion industry nowadays. The next step is 7Ps Marketing Mix. In the 7Ps Marketing Mix, the author proposed to change the marketing strategy of Calamus FO that had made earlier, based on the analysis that has been analyzed by the author. Calamus should develop their superior product (Product), collaborate with radio, hotel, and bank (Promotion), reduce the profit margin (Price), encourage the majority of future purchases by request on market demand by finding local suppliers which offers international trends (Process), suggest to the management to hire people who has ability to redecorate exterior and interior of Calamus FO (Physical evidence), conduct English language lessons for Sales Promotion Boy/Sales Promotion Girl (People), and put the banner in strategic area such as Husein Sastranegara Airport and Pasteur Freeway gate (Place).After the proposal of marketing strategy has been accepted by the management, Calamus FO will implement the strategy starting from the first week of February 2013 until December 2013. The management only takes four recommendations out of seven proposed, because of the finance limitations. The four recommendations are conduct the product procurement based on market demand by finding local suppliers, reduce the profit margin so Calamus FO would be the factory outlet that offers affordable price (cost leadership), and maximize the cooperation or partnership with radio stations, hotels, banks, and travel agents. Based on the marketing strategy, it is expected that Calamus FO will be the new of factory outlet industry in Bandung in terms of price, and it is expected that the targeted revenue that the shareholders want can be achieved.